Where is the African Charter? Assessing the impact of the African Charter on Human and Peoples’ Rights in Mauritius - Gunputh, Rajendra Parsad (University of Pretoria, 2012)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2011.